Production of particleboards with bamboo (Dendrocalamus giganteus) reinforcement - Zaia, Ulysses J.; Cortez-Barbosa, Juliana [UNESP]; Morales, Elen A.M. [UNESP]; Lahr, Francisco A.R.; Do Nascimento, Maria Fátima; De Araujo, Victor A. [UNESP] (BioResources, 2015)
The focus of this research was to study the utilization of residues from bamboo (Dendrocalamus giganteus) lamination in the manufacturing of panels for structural purposes. Bamboo particleboards were produced under three conditions: pure boards, reinforced with bamboo laminas, and with treated particles. Castor oil-based polyurethane was the resin binder, in view of using lower toxicity materials. The mechanical tests were performed according to Brazilian Standard (NBR) 14810-3 (2006) and European Standard (EN) 310 (2000). The results were superior to those recommended by these and other standards for internal adhesion resistance, modulus of rupture, and elasticity in static bending, as well as to the results of other studies. Starch treatment was an unnecessary stage. According to the conditions of this process, the studied panels showed a good potential for construction use. Moreover, the bamboo particleboards are an economically viable, environmentally friendly, and sustainable alternative for the use of waste generated during the processing of Dendrocalamus giganteus bamboo species, allied with castor oil-based polyurethane resin. The reinforced particleboard and its production process are being licensed as an Innovation Patent in Brazil, (BR 1020130133919-1-2013).
Keywords: Bamboo; Castor oil-based polyurethane resin; Particleboards; Reinforcement; Waste